Evaluation Study on Integrated Child Development Schemes (ICDS) Volume II (Appendix) - Planning Commission (Planning Commission, 2011)
Demand Side factors include: AWC far away, Food quality is not good, Family does not allow, Loss of work/ no time & Not aware of services. Supply side factors include: Not distributed, most of the days the food is not available & AWC often remain closed.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India